Sex differences in cognitive function among Chinese older adults using data from the Chinese longitudinal healthy longevity survey: a cross-sectional study - Huang, Xiao; Deng, Jiahui; Liu, Wenbin (Frontiers in Public Health, 2023)
Objective To compare the sex differences in cognitive function and its influencing factors among Chinese older adults. Method We conducted a cross-sectional study by using data from the China Longitudinal Healthy Longevity Survey (CLHLS). According to the 32 provinces and 4 municipalities directly under the Central Government of China, 3–5 counties or districts were randomly selected in each province or city (except Tibet), and then 1–3 villages or streets were randomly selected in each county or district, from which the target population was sampled. Mini Mental State Examination (MMSE) was used to assess the cognitive function of 9,262 older adults aged 65 and above in China. Descriptive analysis was applied to demonstrate the participants’ demographic characteristics, health-related behaviors, social and non-social activity, disease status, mental and sleep condition. And then, univariate and multifactor analyses were performed to validate different risk factors for cognitive function, respectively in the general population, male older adults and female older adults. Result The older adults with cognitive impairment accounted for 10.4% of the total population. There are significant differences in cognitive function between male and female older adults. The odds of cognitive impairment in older adult women was 1.291 times that of older adult men (OR = 1.291, 95%CI: 1.084–1.538). Among the male older adults, those who were older, highly educated, spouseless, had depressive symptoms, and lacked social activities were more likely to have cognitive impairment, whereas among the female older adults, those who were older, highly educated, and lacked social activities were more likely to have cognitive impairment. Conclusion Overall, there are subtle differences in potential influencing factors for cognitive function between the male older adults and female older adults. Attention should be paid to the different cognitive protection measures for the older adults with different sexes.